Screening and verifying the mutations in the LDLR and APOB genes in a Chinese family with familial hypercholesterolemia - Xian Lv; Chunyue Wang; Lu Liu; Guoqing Yin; Wen Zhang; Fuad A. Abdu; Tingting Shi; Qingfeng Zhang; Wenliang Che (Lipids in Health and Disease, 2023)
Abstract Background Familial hypercholesterolemia (FH) is an autosomal dominant genetic disorder. The primary objective of this study was to identify the major pathogenic mutations in a Chinese family with FH. Methods Whole-genome sequencing (WGS) was used to identify variants of FH-related genes, including low-density lipoprotein receptor (LDLR), apolipoprotein B (APOB), and proprotein convertase subtilisin/kexin 9 (PCSK9). Bioinformatics software was used to predict signal peptides, transmembrane structures, and spatial construction information of the mutated sequences. Western blotting was performed on the mutant protein to determine the presence of the major structural domains of the LDLR. The PCSK9 and APOB genes were screened and analyzed. Moreover, the proband and his brother were treated with a PCSK9 inhibitor for 1 year, and the effect of the treatment on lipid levels was assessed. Results WGS revealed two potentially pathogenic mutations in the LDLR gene. One was a novel mutation, c.497delinsGGATCCCCCAGCTGCATCCCCCAG (p. Ala166fs), and the other was a known pathogenic mutation, c.2054C>T (p. Pro685Leu). Bioinformatics prediction and in vitro experiments revealed that the novel mutation could not be expressed on the cell membrane. Numerous gene variants were identified in the APOB gene that may have a significant impact on the family members with FH. Thus, it is suggested that the severe manifestation of FH in the proband primarily resulted from the cumulative genetic effects of variants in both LDLR and APOB. However, a subsequent study indicated that treatment with a PCSK9 inhibitor (Evolocumab) did not significantly reduce the blood lipid levels in the proband or his brother. Conclusions The cumulative effect of LDLR and APOB variants was the primary cause of elevated blood lipid levels in this family. However, PCSK9 inhibitor therapy did not appear to be beneficial for the proband. This study emphasizes the importance of genetic testing in determining the most suitable treatment options for patients with FH.